A Comparative Study of Ticagrelor and Clopidogrel in Patients Undergoing Elective Coronary Stenting - Umer Farooq, Hira Anum, Muhammad Nabeel Akhtar, Ejaz Ul Haq, Khadija Sarwat Farooqui, Ifrah Uroos, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ticagrelor and clopidogrel are widely used P2Y12 inhibitors for patients undergoing percutaneous coronary intervention. While ticagrelor offers faster and more consistent platelet inhibition, its comparative benefit over clopidogrel in elective coronary stenting remains uncertain, especially in local populations. This study evaluated the short-term ischemic and safety outcomes of ticagrelor versus clopidogrel in patients undergoing elective coronary stenting. Methods: A prospective comparative study was conducted at Rehmatul Lil Alameen Institute of Cardiology, Lahore, from January to July 2023. Sixty adults scheduled for elective PCI with drug-eluting stent implantation were enrolled and allocated equally to ticagrelor or clopidogrel, each combined with aspirin. The primary endpoint was 30-day major adverse cardiovascular events including all-cause death, non-fatal myocardial infarction, and ischemia-driven target vessel revascularization. Secondary endpoints included stent thrombosis and safety outcomes such as BARC ≥2 bleeding, access-site complications, dyspnea, and bradyarrhythmias. Analyses were performed using intention-to-treat principles. Results: Baseline demographic and clinical characteristics were comparable between groups. Procedural characteristics, including radial access (91.7 percentage) and procedural success (100 percentage), were similar. At 30 days, major adverse cardiovascular events were lower with ticagrelor compared to clopidogrel (3.3 percentage vs 16.7 percentage, p=0.19). Non-fatal MI (10 percentage) and stent thrombosis (6.7 percentage) occurred only among clopidogrel users. Ticagrelor had higher but non-significant rates of BARC ≥2 bleeding (13.3 percentage vs 3.3 percentage, p=0.35) and dyspnea (20 percentage vs 3.3 percentage, p=0.10). No BARC 3–5 bleeding occurred in either group. Hospital stay and DAPT adherence were similar between groups. Conclusion: Ticagrelor demonstrated a trend toward fewer ischemic complications, including absence of stent thrombosis, without a statistically significant increase in major bleeding at 30 days. Although the study was limited by its small sample size, findings suggest that ticagrelor may offer clinically meaningful ischemic protection in elective PCI settings. Larger multicenter trials are required to clarify the optimal P2Y12 strategy in stable coronary intervention populations. Keywords: Ticagrelor, Clopidogrel, Elective PCI, Major Adverse Cardiovascular Events, Antiplatelet Therapy